2019
DOI: 10.21512/lc.v13i1.5122
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking-Related Challenges to Academic Writing: A Case of Indonesian Postgraduate Students at a UK University

Abstract: This research reported Indonesian students’ perspectives on challenges in writing a critical academic essay and factors causing those challenges in a university in the UK. It was a qualitative method in nature and used a semi-structured interviewing technique with open-ended questions as the main method for data collection. The results indicate four main problems the participants’ encountered in relation to critical thinking realization in their essay writing which include clarity of ideas presented, lack of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Ratnawati, Yuliasri, & Hartono (2018) discovered that undergraduate students in West Java also encountered difficulties in their academic writing. Furthermore, Samanhudi & Linse (2019) found that Indonesian postgraduate students at a UK University faced problems related to critical thinking realization in their essay writing. Azizah & Budiman (2018) observed that postgraduate encountered difficulties in writing paper for international publication.…”
Section: The Process and Problems Of Efl Learners In English Writing:mentioning
confidence: 99%
“…Ratnawati, Yuliasri, & Hartono (2018) discovered that undergraduate students in West Java also encountered difficulties in their academic writing. Furthermore, Samanhudi & Linse (2019) found that Indonesian postgraduate students at a UK University faced problems related to critical thinking realization in their essay writing. Azizah & Budiman (2018) observed that postgraduate encountered difficulties in writing paper for international publication.…”
Section: The Process and Problems Of Efl Learners In English Writing:mentioning
confidence: 99%
“…2 studies are from Southeast Asia, such as Malaysia [3][4][5] [8], and the latter 4 articles are from Iran [11][12] [13]. 2 studies were conducted at well-known colleges in London, UK, but the participants are EFL learners from China, Turkey [1] and Indonesia [14]. Explanatory --Almost all of the previous studies use experimental research incorporating experimental group and control group.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The interviews took place at King's College London, UK with 2 Chinese and 1 Turkey student as the participants as well as interviewees. Another explanatory study that employs semi-structured interviews [14] observes the perspectives of Indonesian postgraduate students studying in a United Kingdom university and the difficulties of expressing their ideas and thoughts in their academic publications. in Iran do not necessarily involve experimental and control groups in testing their participants [13].…”
Section: Methodology Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Indonesian students who come to Australia for pursuing a degree need to deal with several challenges, as they need to adjust the way of learning from memorisation to critical thinking [8]. Most Indonesians students found it challenging to practice critical thinking in oral discussions and also writing assignments.…”
Section: Introductionmentioning
confidence: 99%